Random Number Generator Based on Optimization and Chaotic System - Yildirim, Gokce; Tanyildizi, Erkan (Institute of Electrical and Electronics Engineers Inc., 2023)
In this study, a chaotic system-based random number generator design has been carried out. Differential Evolution optimization algorithm is used in the proposed architecture to determine the initial conditions of the chaotic system, unlike the literature. In this way, while predictability is reduced, an architecture that cannot be solved by reverse engineering has been obtained. At the same time, the entropy pool is expanded by generating different initial conditions. The chi-square hypothesis test has been used to test the performance of the initial conditions obtained as a result of 5 independent runs. The results show that the proposed architecture is successful. © 2023 IEEE.
11th International Symposium on Digital Forensics and Security, ISDFS 2023 -- 11 May 2023 through 12 May 2023 -- TN -- 189042
Keywords: chaotic system; chi-square; differential evolution algorithm; random number generator